A rare case report of Russell's viper snakebite with ischemic stroke. Issue 2 (March 2018) - Pothukuchi, VK; Chepuri, VR; Natta, Kalyani; Madigani, Nagaraju; Kumar, Alok
Ischemic stroke following snakebite is rare. We report a case of a 55-year-old male who developed headache with expressive aphasia following a Russell's viper bite. Computed tomography scan of the brain revealed infarcts in bilateral frontal lobes. The possible mechanisms for cerebral infarction in this scenario are discussed, which include disseminated intravascular coagulation, toxin-induced vasculitis, and endothelial damage. In viper bites, whenever there is any central nervous system manifestations or deficits, immediate computed tomography scan of the brain should be taken to delineate the underlying pathology, whether hemorrhagic or ischemic, as treatments differ in both situations. Although ischemic stroke is rare in viper bites, if the treatment is started early, the neurological deficits can be minimized.